Hypertension and Obesity: Risk Factors for Thyroid Disease - Liu, Feng; Zhang, Xinyu (Frontiers in Endocrinology, 2022)
Thyroid disease instances have rapidly increased in the past few decades; however, the cause of the disease remains unclear. Understanding the pathogenesis of thyroid disease will reduce morbidity and mortality rates. Currently, the identified risk factors from existing studies are controversial as they were determined through qualitative analysis and were not further confirmed by quantitative implementations. Association rule mining, as a subset of data mining techniques, is dedicated to revealing underlying correlations among multiple attributes from a complex heterogeneous dataset, making it suitable for thyroid disease pathogenesis identification. This study adopts two association rule mining algorithms (i.e., Apriori and FP-Growth Tree) to identify risk factors correlated with thyroid disease. Extensive experiments were conducted to reach impartial findings with respect to knowledge discovery through two independent digital health datasets. The findings confirmed gender, hypertension, and obesity are positively related to thyroid disease development. The history of I131 treatment and Triiodothyronine level can be potential factors for evaluating subsequent thyroid disease. Thyroid disease pathogenesis can be revealed with the identified risk factors contributing to mitigated morbidity and mortality rates.